مقارنة بين الظروف المثلى لإنتاج أنزيم السيلّولاز من العزلتين الفطريتين المحليتينT.harzianum و A. alternate - سارة, سناء (Latakia University Journal -Biological Sciences Series, 2016)
تمّ الكشف عن قابلية العزلتين الفطريتين المحليتين Trichoderma harzianum و Alternaria alternate، المعزولتين من المحيط الجذري لنبات القمح Triticum aestivum L.، لإنتاج أنزيم السيلّولاز في الأوساط الصلبة CMC-Agar. فلوحظ أنّ للفطرين قابلية لإنتاج الأنزيم، وتفوق الفطر T.harzianum في إنتاجه للسيلّولاز على الفطر A.alternate. ثمّ أجريّ اختبار كمي باستخدام وسط مندل السائل لتحديد الظروف المثلى من (فترة حضن، درجة حرارة وpH) لأفضل إنتاج للسيلّولاز من الفطرين. فكانت أفضل ظروف لإنتاجه من الفطر T.harzianum هي 7 أيام حضن (3.97 U/mL) ، درجة حرارة 26C (4.07 U/mL) وpH=5.5 (4.19U/mL)، بينما أفضل ظروف لإنتاج السيلّولاز من الفطرA.alternate هي 8 أيام حضن(3.29U/mL)، درجة حرارة 28C (3.15 U/mL) وpH=5.0 (3.86 U/mL). وتبين من المقارنة بين متوسطات الفعالية الأنزيمية لكلا الفطرين تفوّق الفطر T.harzianum بإنتاجه للسيلّولاز على الفطر A.alternate، كما وتبين أنّ تأثير زمن الحضن على إنتاج السيلّولاز من الفطر T.harzianum أكبر من تأثيره على إنتاجه من الفطر A.alternate، في حين تأثير كل من درجة الحرارة ودرجة pH على إنتاج السيلّولاز من الفطر T.harzianum أقل من تأثيرهما على إنتاجه من الفطر A.alternate. It was detected for the ability of a local fungus T.harzianum and A.alternate which was isolated from the rhizosphere of Wheat plant Triticum aestivum L. to produce the enzyme complex cellulase in solid medium (CMC-Agar). So it has been showed that T.harzianum and A.alternate have an ability to produce this enzyme, While the T.harzianum have higher production of cellulase than A.alternate. Then conducted a quantitative test using Mandelium liquid medium is used to determine the optimal conditions (incubation time, temperature, PH) for the best cellulase production of the two fungus studied. It was, the best conditions for its production, from T.harzianum is 7 days inchubation (3.97 U/mL), temperature 26C (4.07 U/mL) and pH=5.5 (4.19U/mL). While the best conditions for its production from A.alternate is 8 days inchubation (3.29U/mL), temperature 28C (3.15 U/mL) and pH=5.0 (3.86 U/mL). The comparison between the enzymatic activity average for both fungus , was showed superiority T.harzianum by production cellulase than fungus A.alternate. And discern that the effect of the incubation time on cellulase production from fungus T.harzianum more than its effect on cellulase production from fungus A.alternate. While effect of pH and temperature on cellulase production from fungus T.harzianum less than their effect on cellulase production from fungus A.alternate.